Acknowledgement to Reviewers of Scientia Pharmaceutica in 2017 - Scientia Pharmaceutica Editorial Office (MDPI AG, 2018)
Peer review is an essential part in the publication process, ensuring that Scientia Pharmaceutica maintains high quality standards for its published papers.[...]